Educational Services Marketing Strategy Based GLS to Increase Customer Interest Study Sequential Exploratory Design Mix Method - Aynun Nurul Ulufah; Prim Masrokan Mutohar; Ahmad Tanzeh; Daud Sukoco (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
Increasing competition among educational institutions requires schools to develop innovative strategies that strengthen institutional competitiveness while attracting prospective students. Although the School Literacy Movement (Gerakan Literasi Sekolah/GLS) has primarily been implemented to improve students' literacy competencies, its role as a strategic educational service marketing approach remains underexplored. This study aimed to analyze the implementation of GLS-based educational service marketing and examine the effects of product differentiation, price differentiation, and promotion differentiation on customer interest at SMA Islam Sunan Gunung Jati Ngunut Tulungagung. A Sequential Exploratory Mixed Methods design was employed by integrating qualitative exploration with quantitative verification. Qualitative data were collected through interviews, observations, and document analysis involving school leaders, teachers, and parents. Quantitative data were obtained from 165 students selected using simple random sampling and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model satisfied the recommended validity criteria with Average Variance Extracted (AVE) values ranging from 0.518 to 0.669. The structural model indicated that product differentiation significantly influenced customer interest (β = 0.179; p = 0.035), price differentiation positively affected customer interest (β = 0.071; p = 0.037), and promotion differentiation showed a positive relationship with customer interest (β = 0.060; p = 0.002). The qualitative findings consistently revealed that literacy-based flagship programs, value-oriented educational pricing, and integrated promotional strategies involving alumni, parents, graduates, print media, and digital platforms strengthened institutional identity and enhanced educational value. The integration of both datasets demonstrates that the School Literacy Movement functions as a strategic educational service marketing framework that increases customer interest and reinforces institutional competitiveness. These findings provide a conceptual contribution by positioning literacy-based educational innovation as a sustainable differentiation strategy for educational institutions.